STUDI PENELITIAN PEMANFAATAN LUMPUR SUNGAI CILIWUNG DENGAN METODE SOLIDIFIKASI - Jeremiah Pasaribu, Roy
River sedimentation potentially lead to siltation of the river and could lead to overflow of river water during the rainy season . This causes water pollution in rivers and streams that can damage itself. Solidification is required for an appropriate processing technology to minimize river sedimentation. This study focuses on the utilization of Ciliwung river sedimentation around the Istiqlal Mosque . From the test results of metal oxide, obtained values of SiO2, Al2O3, and Fe2O3 with a total of 73.81 % DW. Value of 73.81 % DW shows that sludge has pozzolanic properties of compounds containing silica and alumina so it can be used as a fine aggregate in mortar mixing. Solidification products are made with the volume ratio where the ratio of cement to fine aggregates is 1:3, 1:4, and 1:5. The mixture specimens will be molded to the size of 5x5x5 cm3 . In order to know the optimum mix, the selection of 0%, 50%, and 100% amount of sludge as a fine aggregate is selected. 0% selected as the control of solidification test , 50% to determine the compressive strength and maximum control , and 100% was selected to determine the value of the minimum compressive strength test. From the test results, obtained the highest compressive strength values at 216 kg/cm2 at 1:3 variation with sedimentation substitution of 50% and can be used as a quality paving block B (in accordance with SNI 03-0961-1996). The optimum value of compressive strength is 48.8 kg/cm2 at 1:5 with a variation of 100% substitution of sludge and brick can be used as a quality II (in accordance with SNI 03-2113-2000).